ENVIRONMENTAL EDUCATION AS A SYSTEM-FORMING FACTOR IN THE CONCEPT OF SUSTAINABLE DEVELOPMENT (ON THE EXAMPLE OF DAKHADAYEVSKY DISTRICT, DAGESTAN) - G. M. Abdurakhmanov; N. O. Guseynova; S. V. Prokopchik (Юг России: экология, развитие, 2016)
Aim. We aim to analyze the quality of environmental education for sustainable development on the example of secondary schools in Dakhadayevsky district of Dagestan. Methods. As the data for research we used the answers and results on questionnaires and tests held among the students of 5-11 grades of general education institutions in the district. All test materials were compiled at the Institute of Ecology and Sustainable Development, Dagestan State University. Statistical processing of research data was based on well-known techniques and conducted using Excel and Statistica software packages. Results. As a result of the research, we detected low levels of environmental awareness among schoolchildren. A comparative analysis of the level of environmental training of schoolchildren in Dakhadayevsky dictrict showed different results in different villages. It was also revealed that at schools the environmental knowledge is mainly gained in the course of training of biology and to a much lesser extent in the courses of geography and chemistry. The research demonstrates the imperfection of environmental education and hindered transition to a new educational paradigm, which depends on many factors and reflects the general situation of education in Russian schools. Conclusion. We propose to introduce environmental education as a separate discipline into the educational process, as well as a number of relevant topics and methods; to strengthen interdisciplinarity of education in order to learn how to set goals and solve complex social and environmental problems.